(untitled) (Research, Society and Development, 2020)
The objective of the present study was to evaluate the effects of Transcranial Direct Current Stimulation (tDCS) on cognition, functionality and behavioral and psychological symptoms in individuals with Alzheimer’s disease (AD). This is a systematic review, carried out on the basis of Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE (PubMed), Cumulative Index to Nursing and Allied Health Literature (CINAHL), PsycINFO, Scopus, Web of Science, Lilacs and Embase. The publication period of the material used in the present review took into account studies published since its insertion until September 2020. As a result, 759 studies were found, of which 742 were removed according to the eligibility criteria. 17 articles were elected for the complete reading, of which 7 were rejected for not meeting the eligibility criteria. Therefore, 10 studies were selected and included for analysis in this review. Current evidence suggests that tDCS is an alternative therapy for patients with AD. However, the recommendation of this therapy must be performed with caution, since the findings found in the present study indicate low quality of current studies, accompanied by data using small sample sizes and methodological problems, which suggests that more studies are needed to verify clinical efficacy of tDCS in this population.